Projeto e fabricação de uma estrutura modular para o uso em estações meteorológicas de baixo custo - Rockenbach, Fernando Roberto (2019)
Information such as environment temperature, relative humidity, atmospheric pressure, rainfall volume, brightness, wind speed and direction are useful in applications in different areas to monitor, predict and alarm climatic phenomena and allow planning strategic decision making. Weather stations have sensors deployed in remote locations and througha computer system make the collection and storage of the data quickly, practical and frequently. In this way, meteorological stations have assisted in the maximization of agricultural production and reduction of environmental impacts, because through information collected in a field of cultivation it is possible to carry out adequate control of the crop and to obtain a more sustainable development. With the purpose of providing a simple, low-cost and practical weather station to assist in agricultural management, this work has a theoretical basis on the importance of climatic variables and what materials and instructions help to create their own meteorological station to collect data on rainfall volume, direction and wind speed, solar radiation level, ambient temperature, pressure and relative humidity. To assemble the weather station of this work, a metallic structure was used, and some pieces responsible for capturing the time variables were connected to a Raspberry Pi® hardware. Also, a computational module was developed to read the captured data, which was stored on a memory card.The climatic data collected by the meteorological station assembled in this work was compared to the one of a station bought ready and through the statistical analyzes, it was concluded that the prototype assembled in this work was able to collect the climatic data with precision equivalent to season purchased saving of 59% in the final cost.